The Spatiotemporal Dynamics of Morphological Slums in Mumbai, India - John Friesen; Nicolas Johannes Kraff; Hannes Taubenbock (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Our knowledge of the spatial distribution of slums has increased enormously in recent years through research from remote sensing and other sources, although it is still incomplete and fraught with uncertainties. The physical development of slums over time and the estimation of dynamics in the slum population, however, are still little addressed in research. We analyze these dynamics in the South Asian city of Mumbai, India. We capture the spatial extent of slums at the time of three years (2005, 2010, and 2022) using manual visual image interpretation. We merge this spatial information with accepted and globally available gridded population datasets to estimate the population living in morphological slums. We see spatio-temporal dynamics of both areas and population and thereby identify clear trends: instead of showing uncontrolled urban expansion, morphological slums are areas that undergo phases of deconstruction and reconstruction. We see the dynamics are the highest in existing and not in newly emerged slums.